Analysis of the Syllabus of Semiology and Clinical Propedeutics. Steps-structured methodology - natascha mezquia de pedro; Teresa Pérez Díaz; Silvia María Pozo Abreu; Iliovanys Betancourt Plaza; Iraida González Martínez; Arianne Martínez Santiuste (Universidad de Ciencias Médicas de La Habana, 2019)
Introduction: The designs established in the different syllabuses should be in complete agreement with the demands of society. Therefore, an analysis should be carried out in order to improve them permanently. Objective: To determine the scope and limitations of the syllabus of the subject Semiology and Clinical Propedeutics.  Material and Methods:  A qualitative study from a pedagogical perspective was conducted from April 1st to June 31st, 2017, which assumes the materialistic dialectic method with an approach on the system as the main action of the research process in order to carry out a critical syllabus analysis.  The methodology used for this consists of five main steps which include, among other elements, the appropriateness and the review of the components of the teaching-learning process. Results and discussion:  A critical syllabus analysis was carried out, and aspects for the improvement and a didactic unit of contradiction related to the clinical discussion in the medical students were identified at recognizing a disagreement between the subject contents and the ideal way to teach them, thus considering it a methodological problem.  Conclusions:  The curriculum satisfies the integrative idea of Commander Fidel in relation to the teaching-learning process for the formation of doctors in Cuba at advising a comprehensive formation, implementing the in-service training, and increasing the students´ leading role that guarantees a human, scientific, and technical quality, directed to give a better care to the people.  The use of this methodology can be generalized. Keywords: Medical education, syllabus, critics, profile of graduates, Semiology, Clinical Propedeutics.